Developing Class Instruction for Linking The Qur’an to Biological Science - Wasehudin Wasehudin; Darwyan Syah; Mohammad Taufiq Rahman; Uswatun Hasanah (AL-ISHLAH: Jurnal Pendidikan, 2022)
A module book makes all learning activities oriented towards achieving graduate competencies. In particular, the research objectives are following the following stages: 1) building an integrated Al-Quran biology teaching and learning module, 2) testing and evaluating the validity, sensitivity, and effectiveness of science teaching and learning modules on Al-Quran integrated biology subjects, 3) the influence of creative thinking on student achievement among groups of students. Efforts to obtain data on the development of Quran-based science learning modules used for research and development methods. This research design will be carried out, consists of two stages, namely the module construction phase and the module evaluation phase. The module construction phase is carried out through a construction process starting from the initial study, planning, realization, and assessment of the validity of the module. The level of module testing was carried out in the experimental group (EG) and the conventional learning (CL) as the control group. The population of this study was limited to students at two (2) Madrasah Aliyah Negeri Banten Province, namely Madrasah Aliyah Negeri 1 Pandeglang and Madrasah Aliyah Negeri 2 Pandeglang. While the science learning used is the biology subject being studied is biology semester 1 for class XI will be involved in this research. Two of the teachers in the madrasa participated in this study. Al-Quran integrated biology learning module needs to be presented. The effectiveness of the learning module is empirically assessed using the T-test, regression, and correlation.